2013
DOI: 10.1209/0295-5075/102/55002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an external magnetic field on plasma torch discharge fluctuation

Abstract: The effect of an external magnetic field on the anodic arc root movement inside a dc plasma torch has been investigated. In this letter, a virtual instrument technology was used to measure the arc voltage of the plasma torch at atmospheric pressure, and the rotating frequency of the anodic arc root was estimated by high-speed photography. The arc voltage fluctuation which represents the degree of the arc instability was reduced. And a new peak, whose frequency is consistent with the rotating frequency of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Under restrike mode conditions, the anode erosion corresponds to between 5.0 Â 10 À11 and 5.0 Â 10 À10 kg/A.s. Lawton (1971) and Hu et al (2013) studied the effect of a magnetic flux at the cylindrical anode of a torch with a stick type cathode of doped tungsten. The measured voltage waveforms indicated that the arc root attachment mode would be controllable by an external magnetic field.…”
Section: Anode Parallel To the Arc Axismentioning
confidence: 99%
“…Under restrike mode conditions, the anode erosion corresponds to between 5.0 Â 10 À11 and 5.0 Â 10 À10 kg/A.s. Lawton (1971) and Hu et al (2013) studied the effect of a magnetic flux at the cylindrical anode of a torch with a stick type cathode of doped tungsten. The measured voltage waveforms indicated that the arc root attachment mode would be controllable by an external magnetic field.…”
Section: Anode Parallel To the Arc Axismentioning
confidence: 99%
“…One of several methods suggested for improving is to utilize externally applied magnetic field both numerically and experimentally (Sato et al, 2001;Hu et al, 2013;Mostaghimi and Boulos, 2015). Figure 1 shows the schematic diagram of the plasma torch developed by Pershin et al (2013).…”
Section: Introductionmentioning
confidence: 99%